Knitting Love in Pain: A Phenomenon of Dating Violence Among Students of Pattimura University Ambon - Kissya, Rolland; Huliselan, Mus; Koritelu, Paulus (West Science Social and Humanities Studies, 2024)
Dating violence among students is a crucial issue that needs to be addressed promptly so that students can be freed from various acts of dating violence and obtain a safe environment. Therefore, it is important to conduct research, particularly on the factors causing dating violence and the motivation to maintain unhealthy dating relationships among students, in order to fully understand and address this unhealthy dating relationship, minimizing it as its causes are identified. This study adopts a qualitative approach with a descriptive study method, utilizing data collection techniques such as in-depth interviews, documentation, and literature review. Qualitative findings reveal reasons for dating violence among students of the Faculty of Social and Political Sciences as well as the Faculty of Teacher Training and Education at Pattimura University, including internal and external factors such as mindset, unstable emotions, personality, feelings of dependency, and sexual urges. This indicates that forms of violence perpetrated by students include physical, psychological, sexual, and economic violence. The dominant reason why women or victims of violence remain in dating relationships in this study is because they inherit three key indicators of love: voluntary commitment, sacrifice, and forgiveness.